The complete idiot's guide to greening your business - Riley, Trish, 1959-; Gadonniex, Heather; Safari eBooks (Indianapolis, Ind. : Alpha Books, 2009)
"The Complete Idiot's Guide to Greening Your Business gives you ingenious business strategies and practical tips that are good for the environment and save your (large or small) business money. Coverage includes everything from implementing green manufacturing, packaging, and shipping initiatives to collaborating with like-minded businesses and developing staffing strategies that save commuting time and office overhead"--Resource description page.
Greening your business : why it's the way to go -- Getting started on the green path -- Your business environment and operations -- Your business practices and cost benefits -- Marketing your green message.
Description based on print version record.
Includes bibliographical references (p. 313-331) and index.
Keywords: Business enterprises -- Environmental aspects; Industrial management -- Environmental aspects; Social responsibility of business; Electronic books